Energy-saving distillation process for mixed trichlorobenzene based on ORC coupled MVR heat pump technology. (1st January 2023) - Yang, Deming; Wan, Dehao; Yun, Yi; Yang, Shuzhuang
Abstract: Trichlorobenzene is a mixture of three isomers which are 1, 2, 3-trichlorobenzene, 1, 2, 4-trichlorobenzene and 1, 3, 5-trichlorobenzene. Due to the boiling points of the three components are close to each other, the adoption of conventional distillation process requires a large amount of energy. To reduce the distillation energy consumption, heat integration technology and mechanical vapor recompression (MVR) heat pump technology are applied to the separation of the system. Since the waste heat in the MVR heat pump distillation process has not been utilized, the Organic Rankine cycle (ORC) coupled MVR heat pump distillation process was proposed to convert waste heat to electricity for the compressor and the parameters of the ORC system are optimized to determine the optimal working fluid and its parameters. The study results showed that compared with the four-column conventional distillation process, the heat integrated distillation process and MVR heat pump distillation process can reduce energy consumption by 32.7% and 83.5%, save the total annual cost (TAC) by 12.4% and 22.9%; the ORC coupled MVR heat pump distillation process with the best working fluid were R113 and R601a can reduce energy consumption by 18.8% and save TAC by 1.42% compared with the MVR heat pump distillation process. Highlights: Separate mixed trichlorobenzene by distillation instead of crystallization. Heat integration technology, MVR heat pump technology were applied to the energy-saving research. ORC system effectively converts MVR waste heat into electricity.